Preliminary evaluation of a novel method for computed tomography quantification of lumbosacral articular process displacement in dogs with and without degenerative lumbosacral stenosis - Carballo, Oscar; Frederick, Steven W.; Keys, Deborah A.; Moore, Sarah A.; Giles, James T. (Frontiers in Veterinary Science, 2024)
Objective: To describe the diagnostic discrimination and reliability of a novel technique for quantifying lumbosacral articular process displacement (LSAPD) on dorsal plane CT (DPCT) imaging in dogs with and without DLSS. Study Design: DPCT surveys of the lumbosacral vertebral column were performed with dogs positioned in extension and flexion. LSAPD was defined as the distance between the cranial aspects of the L7 and S1 articular processes. The LSAPD-ratio was identified by dividing the LSAPD by the length of the L7 articular process. Intraclass correlation coefficients for intra- and interobserver reliability were calculated, and logistic regressions were used to test for association of LSAPD and LSAPD-ratio with odds of DLSS. Significance was set at 0.05. Receiver operator characteristic (ROC) curves were calculated to determine diagnostic discrimination and optimal cutoff for LSAPD and LSAPD-ratio in the diagnosis of DLSS. Results: Intra- and interobserver reliabilities were excellent for most measurements. In the current cohort, excluding covariates, area under the curve (AUC) (95%CI) for LSAPD and LSAPD-ratio measured in a flexed position were both 0.89 (0.82-0.96) suggesting potentially excellent discrimination for utilizing this measurement as a marker for diagnosing DLSS pending further studies. The cut-offs for flexed LSAPD and LSAPD-ratio that maximizes Youden’s index was >1.2 mm and >9%, respectively. When age and weight were subsequently included as covariates in a multivariable analysis, a significant relationship between LSAPD or LSAPD-ratio and odds of diagnosis of DLSS was not demonstrated, suggesting the need for a larger sample size. Conclusion: Results of this study suggest that measurements of LSAPD and LSAPD-ratios on DPCT are feasible and reliable, although their diagnostic discrimination in DLSS should be evaluated further in future prospective studies.